Carbonyl-coordinating polymers for high-voltage solid-state lithium batteries: Solid polymer electrolytes. (2020) - Xu, Hongli; Xie, Jingbing; Liu, Zhongbo; Wang, Jun; Deng, Yonghong
ABSTRACT: ABSTRACT: Solid polymer electrolytes are a crucial class of compounds in the next-generation solid-state lithium batteries featured by high safety and extraordinary energy density. This review highlights the importance of carbonyl-coordinating polymer-based solid polymer electrolytes in next-generation safe and high–energy density lithium metal batteries, unraveling their synthesis, sustainability, and electrochemical performance. With the massive consumption of fossil fuel in vehicles nowadays, the resulted air pollution and greenhouse gases issue have now aroused the global interest on the replacement of the internal combustion engines with engine systems using renewable energy. Thus, the commercial electric vehicle market is growing fast. As the requirement for longer driving distances and higher safety in commercial electric vehicles becomes more demanding, great endeavors have been devoted to developing the next-generation solid-state lithium metal batteries using high-voltage cathode materials, e.g., high nickel (Ni) ternary active materials, LiCoO2, and spinel LiNi0.5 Mn1.5 O4 . However, the most extensively investigated solid polymer electrolytes (SPEs) are based on polyether-based polymers, especially the archetypal poly(ethylene oxide), which are still suffering from low ionic conductivity (10 −7 to 10 −6 S/cm at room temperature), limited lithium ion transference number (<0.2), and narrow electrochemical stability window (<3.9 V), restricting this type of SPEs from realizing their full potential for the next-generation lithium-based energy storage technologies. As a promising class of alternative polymer hosts for SPEs, carbonyl-coordinating polymers have been extensively researched, exhibiting unique and promising electrochemical properties. Herein, the synthesis, sustainability, and electrochemical performance of carbonyl-coordinating SPEs for high-voltage solid-state lithium batteries will be reviewed.